2012
DOI: 10.2147/ijn.s37022
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and in vitro release behavior of a novel antibacterial coating containing halogenated furanone-loaded poly(L-lactic acid) nanoparticles on microarc-oxidized titanium

Abstract: Background: Dental implants have become increasingly common for the management of missing teeth. However, peri-implant infection remains a problem, is usually difficult to treat, and may lead eventually to dental implant failure. The aim of this study was to fabricate a novel antibacterial coating containing a halogenated furanone compound, ie, (Z-)-4-bromo-5-(bromomethylene)-2(5H)-furanone (BBF)-loaded poly(L-lactic acid) (PLLA) nanoparticles on microarc-oxidized titanium and to evaluate its release behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Furanones were also loaded into microparticles [26] and nanoparticles [27]. Specifically, Cheng et al [27] used the halogenated 4-bromo-5-(bromomethylene)-2(5H)-furanone in combination with biodegradable poly-DL-lactic acid nanoparticles to fabricate a novel antibacterial coating for titanium (Ti) implants. Ti material may also be used for tympanostomy tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Furanones were also loaded into microparticles [26] and nanoparticles [27]. Specifically, Cheng et al [27] used the halogenated 4-bromo-5-(bromomethylene)-2(5H)-furanone in combination with biodegradable poly-DL-lactic acid nanoparticles to fabricate a novel antibacterial coating for titanium (Ti) implants. Ti material may also be used for tympanostomy tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of functional groups in propanoic acid such as hydroxyl groups, ethylene oxide, carbonyl, double bonds, benzene rings, oxygen atoms, nitrogen atoms in addition to the hydrophobic chain of the surfactant is responsible for increasing its adsorption ability on the steel surface (Abd-Elaal et al 2018). Furanon compounds have the potential to inhibit microbial corrosion associated with Gram-positive bacteria (Srinivasan et al 2021;Wu et al 2012). Based on previous research, it was found that the addition of a concentration of 40 mg/ml furanone was able to inhibit the growth of Desulfotomaculum orientis (a microbe that causes corrosion) by 96% (Ren et al 2001).…”
Section: Bioactive Compounds Of Propolismentioning
confidence: 99%
“…This period is considered long enough to prevent implant-associated infections during the initial stages of device implantation. 9799…”
Section: Preventive Strategies For Implants Associated Infectionsmentioning
confidence: 99%
“…This period is considered long enough to prevent implant-associated infections during the initial stages of device implantation. [97][98][99] Nitric oxide-releasing coatings: Nitric oxide is wellrecognized for its activity in the inhibition of platelets adhesion and activation therefore nitric oxide coatings on silicone, polyurethane and polymethacrylate can be potentially used as thrombo-resistant coatings on many biomedical devices including in vivo sensors, catheters, stents, arteriovenous grafts, and extracorporeal circuits. Moreover, the anti-biofilm activity of nitric oxide has been proved and therefore may be used for the development of antimicrobial/antithrombotic CVCs because of the double effect of nitric oxide.…”
Section: Implants Coatings With Antimicrobial Agentsmentioning
confidence: 99%